Sequence analysis of RAS and RAF mutation hot spots in canine carcinoma. (6th October 2016) - Mochizuki, H.; Breen, M.
Abstract: Recent discovery of the BRAF V595E mutation in a variety of canine cancers indicates that mutant BRAF may represent a novel therapeutic target. Presence of RAS mutations is associated with poor tumour response to BRAF inhibition but has not been investigated in BRAF ‐mutated canine cancers. The aim of this study was to evaluate the mutational status of three RAS genes ( HRAS, KRAS and NRAS ) in four types of canine carcinoma with and without the BRAF V595E mutation. Novel HRAS mutations were identified in 18% (3/17) of oral squamous cell carcinoma, whereas 17% (3/18) of pulmonary carcinoma carried KRAS or NRAS mutations. These RAS mutations and BRAF V595E were mutually exclusive, indicating similar functional consequence of these mutations (e.g. MAPK pathway activation). In contrast, RAS mutations were absent in 39 urothelial carcinoma and 19 prostatic carcinoma, adding another rational for BRAF‐targeted therapy for these canine cancers.